Upaya Pemerintah Dalam Membangun Rekonsiliasi dan Pencegahan Konflik Sejak Dini Di Kalimantan Barat - Syamsuwir, Syamsuwir; Fakhrurrazi, Fakhrurrazi (Universitas Malikussaleh, 2014)
Talking about Government Efforts in Building Reconciliation and Conflict Prevention in West Kalimantan since Dini, the vision of